2008
DOI: 10.1073/pnas.0807461105
|View full text |Cite|
|
Sign up to set email alerts
|

Left-right asymmetry of the hippocampal synapses with differential subunit allocation of glutamate receptors

Abstract: Left-right asymmetry of the brain has been studied mostly through psychological examination and functional imaging in primates, leaving its molecular and synaptic aspects largely unaddressed. Here, we show that hippocampal CA1 pyramidal cell synapses differ in size, shape, and glutamate receptor expression depending on the laterality of presynaptic origin. CA1 synapses receiving neuronal input from the right CA3 pyramidal cells are larger and have more perforated PSD and a GluR1 expression level twice as high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
193
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(204 citation statements)
references
References 26 publications
11
193
0
Order By: Relevance
“…Kawakami et al 37 observed an asymmetric synaptic distribution of N-methyl-D-aspartate receptor between the left and right adult mouse hippocampus. Shinohara et al 38 reported that hippocampal CA1 synapses, which receive neuronal input from the right CA3 pyramidal cells are larger and have markedly higher expression level from glutamate receptor GluR1 than those which receive input from the left CA3. Thus, we can only speculate that this lateralized molecular pattern might have contributed to our findings.…”
Section: Spectroscopic Resultsmentioning
confidence: 99%
“…Kawakami et al 37 observed an asymmetric synaptic distribution of N-methyl-D-aspartate receptor between the left and right adult mouse hippocampus. Shinohara et al 38 reported that hippocampal CA1 synapses, which receive neuronal input from the right CA3 pyramidal cells are larger and have markedly higher expression level from glutamate receptor GluR1 than those which receive input from the left CA3. Thus, we can only speculate that this lateralized molecular pattern might have contributed to our findings.…”
Section: Spectroscopic Resultsmentioning
confidence: 99%
“…Although some reports start to show an intriguing bilateral asymmetry in rat hippocampus [88][89][90][91], little is known about its functional relevance. Two commissural systems connect the hippocampus, the CA3 contralateral projection to CA1, CA2 and CA3, and the contralateral DG projection mainly formed by hilar mossy cells (MCs).…”
Section: (F ) Enhanced Interhemispheric Communicationmentioning
confidence: 99%
“…25,30 Intriguingly, our observation of left lateralized volume differences is also consistent with work in animals and tissue culture experiments on NMDA receptor subunits. NMDA receptors that contain NR2B subunits are more densely expressed in the left hippocampus than in the right, 31,32 and NMDA-mediated excitotoxicity is dependent on NMDA receptors containing NR2B subunits. 33 Therefore, the left hippocampus may be more susceptible to excitotoxicity-induced injury.…”
Section: Discussionmentioning
confidence: 99%